CYTOLOGICAL EVALUATION OF MALE BREAST LESIONS: RETROSPECTIVE ANALYSIS IN NORTHERN STATE OF INDIA. - Aruna Gupta; Saurabh Sharma; Garima Thapa; Vikas Gupta (Student’s Journal of Health Research Africa, 2023)
Background: Symptoms of breast sickness commonly include breast discomfort, nipple discharge, and palpable breast lumps. Breast cytology, which involves fine-needle aspiration, nipple discharge smear, and touch preparation, may accurately assess breast specimens. This study’s goals are to categorize the different cancers of the breast that breast cytology can diagnose and to assess the clinical sufficiency of narrative reporting of breast cytology results. Methods: The medical files of 390 patients who visited the general surgery clinics at the Rajendra Prasad Medical College, Tanda within five years underwent retrospective analysis. Results: Neoplastic breast lesions accounted up 75.9% of the overall number of breast lesions, however, all diagnostic breast lesions (n = 94) were non-neoplastic. The ratio of benign to malignant lesions was 2.6:1, with 72.3% of benign and 27.7% of malignant lesions among the neoplastic lesions (n = 214). Gynecomastia (n = 33) and fibroadenoma (n = 136) were the most frequently diagnosed breast lesions in both men and women. Conclusions: Both malignant and non-cancerous breast lesions were correctly detected by breast cytology. By comparing our findings with previous observations made by other authors, the conclusion that was drawn was that women were more likely than men to develop neoplastic breast lesions, whereas men were more likely to develop non-neoplastic lesions. Recommendation: This hospital is advised to implement a synoptic reporting format that includes the diagnostic categories (C1 to C5) of the United Kingdom’s National Health Service Breast Screening Programme in order to resolve the issues related to narrative reporting of breast cytology results.